Challenging behaviour in school – special education teachers’ perceptions - Hämeenaho, Pilvi (Special Education, 2016)
This article explores the challenges that special education teachers encounter during their daily work in Finnish schools. The main focus is in those challenges which cause worry among teachers, especially aggressive behavior in class rooms and school area. This article scrutinizes the reasons and consequences of a problem from the perspective of special education teachers. The research shows, how problems are mainly caused by delays in assessments, treatments and rehabilitation for pupils with mental or behavioral disorders. The analysis shows how on teachers’ opinion, challenging situations, which induce great worry occur when pupil has a need for psychiatric treatment but had not received it in time. In these kind of situations teachers feel frustrated and partly helpless as their professional skills and knowledge is not enough to provide the support pupil needs. When the neediest pupils do not receive support and treatment in time, it leads to situation where special education teachers have to provide support and face pupils’ challenging behavior even if they may not have measures for it.